Road Traffic Injuries and Related Safety Measures: A Multicentre Analysis at Military Hospitals in Tabuk, Saudi Arabia - Umar Yagoub; Nasrin S. Saiyed; Bahaa-eldin E. A. Rahim; Nizar Musawa; Attiya Mohammed Al Zahrani (Emergency Medicine International)
Background. Road traffic injuries are one of the major public safety issues around the world, as they put a great burden on countries’ economies. Saudi Arabia has a good road transportation system, but still, road-related fatalities are higher in this country. The main purpose of this study was to determine the association between the severity of injuries caused by road traffic collision and safety measures taken by the drivers admitted to the emergency departments at two military hospitals in Tabuk, a city in Saudi Arabia. Methods. A total of 342 male drivers who had injuries due to road traffic collision took part in this multicentre, cross-sectional study. The research sites were King Salman Armed Forces Hospital and King Khalid Armed Forces Hospital in Tabuk, Saudi Arabia. The data were collected using a common protocol and a self-reported questionnaire with the help of convenience sampling approach. Descriptive statistics and logistic regression analysis were done using IBM SPSS version 23. Results. Nearly 62.0% of the male drivers were aged less than 36 years. About 90% of the drivers were from low- and middle-income groups. Logistic regression analysis indicated that drivers who had road traffic collision and used mobile phones while driving were four times more likely to have severe injuries (OR = 3.89; 95% CI (2.53, 5.95)), those who drove the vehicle at an excessive speed limit were three times more likely to have severe injuries (OR = 2.71; 95% CI (1.01, 4.97)), and those who attempted to overtake another vehicle were two times more likely to have severe injuries (OR = 1.85; 95% CI (1.24, 3.77)). Conclusion. Based on the results of the present study, the most important safety measures which contributed the most to road traffic collision were use of mobile phones while driving the vehicle, driving at an excessive speed limit, irregularity in maintaining the vehicle, attempt to pass other vehicles, and not following the traffic rules. All the safety measures are protective, but if care is not taken, they will risk the life. There is an urgent need to spread traffic safety awareness in this region.